2018
DOI: 10.1002/jbio.201800089
|View full text |Cite
|
Sign up to set email alerts
|

Functional optical coherence tomography of neurovascular coupling interactions in the retina

Abstract: Quantitative evaluation of retinal neurovascular coupling is essential for a better understanding of visual function and early detection of eye diseases. However, there is no established method to monitor coherent interactions between stimulus-evoked neural activity and hemodynamic responses at high resolution. Here, we report a multimodal functional optical coherence tomography (OCT) imaging methodology to enable concurrent intrinsic optical signal (IOS) imaging of stimulus-evoked neural activity and hemodyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 51 publications
3
41
0
Order By: Relevance
“…These studies showed variations in response depending on the stimulus conditions, consistent with what is known of retinal visual processing 7 . In rodents similar results are found with flicker-evoked increases in flow in both mice, using optical coherence tomography angiography 8,9 and rats, using fluorescein angiography 10 . For humans neurovascular coupling has been intensively investigated in the brain 11,12 , where it is the source of the BOLD signal that underlies fMRI 13 as well as in the retina using noninvasive imaging.…”
supporting
confidence: 78%
“…These studies showed variations in response depending on the stimulus conditions, consistent with what is known of retinal visual processing 7 . In rodents similar results are found with flicker-evoked increases in flow in both mice, using optical coherence tomography angiography 8,9 and rats, using fluorescein angiography 10 . For humans neurovascular coupling has been intensively investigated in the brain 11,12 , where it is the source of the BOLD signal that underlies fMRI 13 as well as in the retina using noninvasive imaging.…”
supporting
confidence: 78%
“…33 IOS imaging of laser-injured frog eyes demonstrated that the confocal IOS can clearly detect localized (30 mm) functional lesions in the retina before morphological abnormality is detectable. 53 Depth-resolved in vivo OCT imaging of stimulus-evoked IOS changes in frog 58 and mouse 30,57 retinas further showed that the fast IOS changes were primarily observed at the photoreceptor layer, particularly the OS region. With increased stimulus duration or repeated flash stimuli, IOS changes were also detected in the inner retinal layers.…”
Section: In Vitro Imaging Of Photoreceptor-iosmentioning
confidence: 97%
“…A recent comparative study of wild-type (WT) and retinal degeneration 10 (rd10) mice demonstrated that fast photoreceptor-IOS occurs even earlier than PDE activation. 46 In vivo imaging of photoreceptor-IOS Modified fundus camera, [47][48][49][50] adaptive optics, 51,52 confocal, 53,54 and OCT 30,[55][56][57][58][59][60][61] systems have been explored for in vivo retinal IOS imaging of anesthetized animals 30,[47][48][49][50]53,54,[57][58][59] and awake humans. 51,52,55,60,61 A high-speed (200 frames/s) line-scan confocal ophthalmoscope has been used to demonstrate in vivo IOS imaging of intact frog eyes.…”
Section: In Vitro Imaging Of Photoreceptor-iosmentioning
confidence: 99%
“…With the 10-ms visible light flash stimulation, the IOS changes were primarily observed at the photoreceptor layer, particularly the outer segment (Figure 6(e) and (f)). With increased stimulus duration, 24 or repeated flash stimuli, 27 i.e. flicker stimulation, stimulusevoked IOS changes were also observed in inner retinal layers.…”
Section: Functional Oct Imaging Of Retinal Activationmentioning
confidence: 99%
“…Scale bars in (a1) and (b1) indicate 500 mm. Modified with permission from Son et al27 (A color version of this figure is available in the online journal. )…”
mentioning
confidence: 99%